Structure-based assortment of herbal analogues against spike protein to restrict COVID-19 entry through hACE2 receptor: An in-silico approach - Santra, Sourav; Das, Sasti Gopal; Halder, Suman Kumar; Ghosh, Kuntal; Banerjee, Amrita; Panda, Amiya Kumar; Mondal, Keshab Chandra (Acta Biologica Szegediensis, 2021)
On-going global pandemic COVID-19 has spread all over the world and has led to more than 1.97 million deaths till date. Natural compounds may be useful to protecting health in this perilous condition. Mechanism of shuttle entry of SARS-COV-2 virus is by interaction with viral spike protein with human angiotensin-converting enzyme-2 (ACE-2) receptor. To explore potential natural therapeutics, 213 important phytochemi-cals of nine medicinal plants Aconitum heterophyllum, Cassia angustifolia, Cymbopogon flexuosus, Cymbopogon martinii, Nux vomica, Phyllanthus urinaria, Swertia chirayita, Justicia adhatoda, Vetiveria zizanioides were selected for in-silico molecular docking against the spike protein of SARS-COV-2 and compared with recently prescribed drug chloroquine, ramdesivir, lopinavir and hydroxychloroquine. Results revealed that rhamnocitrin of P. urinaria, 1,5-dihydroxy-3,8-dimethoxyxanthone of S. chirayita and laevojunenol of V. zizanioides potentially binds with the receptor binding site of SARS-COV-2 spike glycoprotein and more robustly destabilized the RBD-ACE-2 binding over chloroquine, ramdesivir, lopinavir and hydroxychloroquine. It was also found that laevojunenol, rhamnocitrin, and 1,5-dihydroxy-3,8-dimethoxyxanthone qualiﬁed the criteria for drug-likeness as per Lipinski rule. After attachment of the selected phytochemical with the spike protein the aﬃnity of the later towards ACE-2 was minimized and the eﬀect of 1,5-dihydroxy-3,8-dimethoxyxanthone and laevojunenol was superior. Hence, rhamnocitrin of P. urinaria, 1,5-dihydroxy-3,8-dimethoxyxanthone of S. chirayita and laevojunenol of V. zizanioides, are potential therapeutic molecules for SARS-COV-2, which upon binding with spike protein changes the aﬃnity of the spike towards ACE-2 and therefore restrict the entry of the virus into a human cell. Subsequent clinical validation is needed to conﬁrm these phytochemicals as drugs to combat COVID-19.